Acute administration of MK-801 in an animal model of psychosis in rats interferes with cognitively demanding forms of behavioral flexibility on a rotating arena - Svoboda, Jan; Stankova, Anna; Entlerova, Marie; Stuchlik, Ales (Frontiers in Behavioral Neuroscience, 2015)
Patients with schizophrenia often manifest deficits in behavioral flexibility. Non-competitive NMDA receptor antagonists such as MK-801 induce schizophrenia-like symptoms in rodents, including cognitive functions. Despite work exploring flexibility has been done employing behavioral paradigms with simple stimuli, much less is known about what kinds of flexibility are affected in an MK-801 model of schizophrenia-like behavior in the spatial domain. We used a rotating arena-based apparatus (Carousel) requiring rats to avoid an unmarked sector defined in either the reference frame of the rotating arena (arena frame task, AF) or the stationary room (room frame task, RF). We investigated behavioral flexibility in four conditions involving different cognitive loads. Each condition encompassed an initial (five sessions) and a test phase (five sessions) in which some aspects of the task were changed to test flexibility in which rats were given saline, 0.05 mg/kg or 0.1 mg/kg MK-801 thirty minutes prior to a session. In the first condition, rats acquired avoidance in RF with clockwise rotation of the arena while in the test phase the arena rotated counterclockwise. In the second condition, rats initially acquired avoidance in RF with the sector on the north and then it was reversed to south (spatial reversal). In the third and fourth conditions, rats initially performed an AF (RF, respectively) task, followed by an RF (AF, respectively) task, testing the ability of cognitive set-shifting. We found no effect of MK-801 either on simple motor adjustment after reversal of arena rotation or on spatial reversal within the RF. In contrast, administration of MK-801 at a dose of 0.1 mg/kg interfered with set-shifting in both conditions. Furthermore, we observed MK-801 0.1 mg/kg elevated locomotion in all cases. These data suggest that blockade of NMDA receptors by acute system administration of MK-801 preferentially affects set-shifting in the cognitive domain rather than reversal.